Kinematics in elite kayakers while paddling a sliding ergometer equipped with standard and swivel seats - Fohanno, V.; Colloud, F.; Mansour, K. B.; Lacouture, P. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
This study investigated the effects of two seat designs (standard versus swivel seats) at two paces (training and race paces) on the main kinematics parameters involved in kayaking performance. Eight elite athletes performed two trials at an incremental stroke rate. Sixteen markers were recorded by a motion capture system. Angular (trunk) and linear (blade tips) kinematics were calculated during aquatic phase. A Wilcoxon signed-rank test was carried out to compare seat conditions. Results indicated a significant increase of pelvis and thorax rotations associated with both greater mediolateral displacements and velocities of the blade tips at both paces. However, complex interactions may limit these positive effects. While paddling on-water, the performance in competition was not improved significantly with the introduction of the swivel seat.